Self-control profile of students in implementing discipline in school - Nur Damayanti; Asmidir Ilyas (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
Discipline is the most important thing for students to succeed in learning. Therefore, students are expected to have high self-control in order to avoid negative behavior. The purpose of this study was to describe behavioral control, cognitive control and decision control of students in carrying out discipline. This research is a descriptive study, the entire population of students of class X and XI in SMKN 1 Kotanopan and as many as 260 samples obtained by 158 students. This research instrument was a questionnaire. Research findings reveal student’s self-control in carrying out discipline in SMKN 1 Kotanopan been good. Suggested to the Guidance and Counseling teacher to provide service and develop programs to improve student’s self-control.